Prevalence and characteristics of plateau iris configuration among American Caucasian, American Chinese and mainland Chinese subjects. Issue 4 (15th January 2014) - Li, Yingjie; Wang, Ye Elaine; Huang, Guofu; Wang, Dandan; He, Mingguang; Qiu, Mary; Lin, Shan
Abstract : Background: To investigate the prevalence, risk factors and characteristics of plateau iris configuration (PIC) among American Caucasian, American Chinese and mainland Chinese. Methods: This multicentre, cross-sectional study of non-glaucomatous subjects (40–80 years) included 111 American Caucasian, 116 American Chinese and 110 mainland Chinese. Prevalence of PIC based on ultrasound biomicroscopy imaging was compared among the different ethnic groups. Risk factors and anterior segment optical coherence tomography-measured iris and angle parameters in eyes with PIC were compared. Results: The prevalence of PIC was 25.2% in American Caucasian, 24.1% in American Chinese and 20.9% in mainland Chinese (p=0.73). The presence of PIC was associated with more positive spherical equivalence (OR=1.31, p=0.002) and shorter axial length (OR=0.75, p=0.04). There were significant differences in angle recess area (ARA) (p=0.04), IT750 (p=0.007) and IT2000 (p<0.001) between Chinese and Caucasians who have PIC. Conclusions: The prevalence of PIC did not differ among American Caucasian, American Chinese and mainland Chinese. PIC was associated with non-myopia and shorter axial length. Chinese eyes with PIC had smaller ARA and thicker irides than Caucasian ones. PIC might be a physiological variation of the iris and ciliary body that exists in normal eyes, both in Chinese and Caucasians.